Usos do livro didático de letramento e alfabetização pelos professores nos anos iniciais do Ensino Fundamental - Giane Maria da Silva (2016)
This research aims to describe and analyze the uses that three teachers of a public school of Minas Gerais - Brazil, who worked in the early years of elementary school, made of a didactic collection of alphabetization and literacy during a school year. According to the latest changes in the Programa Nacional do Livro Didático (PNLD), a National Textbook Program, due to the new demands made in the reorganization of the Nine Year Basic Education and the constitution of a cycle for the first three years of this segment, this study aims to reveal therole of the didactic book in the pedagogical practice of those teachers. Through a qualitative approach, we grouped various strategies such as observation of classes in daily notes and interviews with the teachers. The research, made especially based on De Certeau studies(2003), through his concepts of strategy and tactics, and Chartier studies (1998, 2000, 2007), with her concept of practice, showed that the textbooks are present in literacy classes, but there is a distance between what is expected of working with a collection that had good evaluation, approved by PNLD, and its effective use in the classroom. This distance is noticeable among the large volume of copies distributed for Brazilian public schools and its underutilization, or even denial of use of this material in the classroom. And there are also, due to the cunning and creativity of the teachers, proposals for transformation of activitiespresented by the textbook adopted, through the action of these professionals in their teaching practice and appropriations that they make of the material. Parallel to the work done with the adopted textbooks, other printed works, as fragments of other textbooks, handbook materials -purchased by teachers with their own resources and also extracted activities of blogs, constituted strong presence in all the three classes. The study also showed that teachers were not passive in the face of proposals presented by the textbook. Each one, in her own way,overthrew its use, adapting it to their needs in the classroom and in accordance with the profile of their students. This adjustment good or bad was intended to reach the needs of groups at that particular moment.